The effects of COVID-19 lockdown on the perception of physical activity and on the perception of musculoskeletal symptoms in computer workers: comparative longitudinal study design - Moreira, Sara (2022)
Lockdown resulting from the pandemic led to a change in the health habits of the computer workers community. Sedentary work, together with less active lifestyles, aggravated by the COVID-19 pandemic leads to impacts on physical activity (PA) and can contribute to the development of musculoskeletal symptoms (MSS). Aim(s): Understand the effects of lockdown on the perception of physical activity levels and on the perception of frequency of musculoskeletal symptoms, over periods of 12 months and 7 days, in computer workers. Methods: Longitudinal comparative study between 2019 (M1) and 2021 (M2), over 18 months, in 40 volunteer participants. The inclusion criteria were full-time workers aged between 18 and 65 and the exclusion criteria included diagnosis of non-work-related medical conditions. In addition to a socio-demographic questionnaire, the Nordic musculoskeletal questionnaire (NMQ) was used to evaluate the MSS and the International Physical Activity Questionnaire (IPAQ), was used to analyse the perception of the level of PA. These questionnaires were used in two assessment stages (M1 and M2). McNemar test and Wilcoxon paired test were used to evaluate the effect of lockdown on the perception of PA, and on the perception of frequency of musculoskeletal symptoms. Results: The MSS prevalence in the previous 12 months increased significantly in the neck (M1: 45.0%, M2: 62.5%, p = 0.046), in the shoulders (M1: 37.5%, M2: 55.0%, p = 0.033), and in the hands/wrists (M1: 25.0%, M2: 45.0%, p = 0.019). The mean pain score increased in the shoulders (1.43 ± 2.24, 2.35 ± 2.55, p = 0.003) and in the elbows (0.18 ± 0.59, 0.60 ± 1.34, p = 0.015). No differences were found in the PA between M1 and M2, but the weekly mean sitting time increased from 4.75 ± 2.26 to 6.26 ± 2.65 (p < 0.001). Conclusion: After 18 months it became clear that MSS perception increased mainly in the neck, shoulders and hands/wrists with a significant increase in pain intensity in the shoulder and elbow regions. The weekly sitting time increased significantly. Further studies are needed in order to determine the impact of teleworking in a pandemic context. But multifactor behind these results should be taken into account by health institutions and those responsible for the Prevention of Occupational Risks in Computer Workers in order to adopt educational strategies for the promotion of Physical activity (PA), in these workers.